Entrepreneural success from positive psychology view - Juhdi, Noor Hasni; Juhdi, Nurita (2013)
Entrepreneurial success should be viewed as a virtuous life mission that needs to be re-conceptualized. It was suggested in this study that entrepreneurial success should be more than just financially termed, based on positive psychology view. Psychological measures of success were asserted to be the next vital domain indicating entrepreneurial success besides financial measures. This study was essential because the findings could lead to more explorations of vital factors that lead to entrepreneurial success and to more comprehensive entrepreneurship theory in future research. Psychological states variables such as psychological capital and entrepreneurial work engagement were identified as the relevant factors to partly explain entrepreneurial success as conceptualized in this study. This research discussed entrepreneurial success from the perspectives of established entrepreneurs in Malaysia. The sample of entrepreneurs was drawn from a frame, which consisted of at least 502 small and medium service enterprises. The findings showed that both psychological capital and entrepreneurial work engagement were directly related to psychological measures of success but were moderately correlated to financial performance. The proposed domains, financial performance and psychological measures of success, were positively correlated as indicators of entrepreneurial success.